Analysis of indicators for monitoring patients having chronic diseases: a cost reduction strategy - Claudia Raffa Galvão; Luis Hernan Contreras Pinochet; Mariza Alves Vieira; Ronaldo Miquelão (O Mundo da Saúde)
The present research aimed at verifying whether the Monitoring Program for Chronic Diseases Patients is an efficient way for reducing the costs of treatment of patients and, simultaneously, verifying the capacity to reduce re-internment rates, extending, thus, the levels of knowledge of managers of the area as regards measures for health promotion and prevention as ways for reducing costs. The methodology adopted was field research of an exploratory and descriptive nature, analyzing data of 30 patients enrolled in the monitoring program, divided in three groups: patients having cardiovascular diseases, patients having lung diseases and patients having Diabetes mellitus. After the analysis of gathered data, it was possible to verify that the implantation of the program produced a significant reduction of costs in the first two years, mainly in the group of patients with lung diseases, as well as a reduction in re- -internment rates of these patients. The other groups also analyzed had demonstrated a reduction in the costs with their treatment and a reduction in rates of re-internment, but in a lesser degree. One concluded that the Monitoring Program for Chronic Diseases Patients is an efficient way for reducing costs.